Speech Recognition and Temporal Processing in Middle-Aged Women - Helfer, Karen S. (2009)
PURPOSE: This study was designed to examine speech understanding ability and temporal processing in middle-aged women with normal or near-normal pure-tone thresholds. RESEARCH DESIGN: Speech understanding, temporal processing ability, and self-assessed hearing were measured in groups of younger and middle-aged females. STUDY SAMPLE: Participants were younger and middle-aged females (n = 12 per group) with normal hearing through 4000 Hz bilaterally. Subjects were drawn from nonclinical populations. DATA COLLECTION AND ANALYSIS: Speech understanding was measured in the presence of steady-state noise and competing speech, with and without perceived spatial separation of the target speech and masker. The Gaps-In-Noise (GIN) test (Musiek et al, 2005) was used to assess temporal resolution ability. In addition, subjects completed a questionnaire with several items from the Speech, Spatial, and Qualities of Hearing Scale (Gatehouse and Noble, 2004) to gauge their subjective ability to understand speech in complex listening situations. Data were analyzed via repeated-measures ANOVA and Pearson r correlations. RESULTS: Results showed that the performance of the middle-aged subjects was significantly poorer than that of the younger participants in the presence of a spatially coincident speech masker. Although performance in this listening condition was unrelated to pure-tone thresholds, it was strongly correlated with scores on the GIN test. Speech understanding performance in the presence of a steady-state masker was related to high-frequency pure-tone thresholds. CONCLUSIONS: These results suggest that some middle-aged women with little or no pure-tone hearing loss experience listening difficulty in complex environments. Results also suggest a strong relationship between temporal processing and speech understanding in certain competing speech situations.